A modified ferron method for aluminum determination - Kubota, Lauro T.; Miyazawa, Mario; Ishikawa, Dilson N.; Pavan, Marcos A. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to modify the ferron method for aluminum determination in soil and plant extracts in order to avoid iron interferences. The differences between spectrophotometric measurements of the Al-Fe-ferron and Al-ferron complexes at 370 nm and 600 nm by the original method, were found to be variable and higly dependent on Fe levels in solution. The Fe-ferron complex did not follow Beer's law at 370 nm and the absorbance was not proportional to that at 600 nm. A modification of the ferron method for the determination of Al in the presence of Fe is described in which the interfering effect of Fe ions is suppressed by masking with a complexone solution of 1,10-phenantroline after reduction of Fe3+ to Fe2+ with NH3OHCl. The differences between absorbances of Al-Fe-fer.-phen and Al-fer.-phen, measured at 370 nm and 530 nm, were constants for a wide range of Al and Fe concentrations in solutions. The modified method is precise and accurate for determining extractable Al from soil (1 M KCl, 0.01 M CaCl2 and 1 N NH4OAc pH 4.8) and total Al from plant (Nitric-perchloric digestion) extracts. The results of the modified method were similar to those determined by the eriochrome cyanine method.